Oncoprotein CIP2A promotes the disassembly of primary cilia and inhibits glycolytic metabolism. (28th February 2018) - Jeong, Ae Lee; Ka, Hye In; Han, Sora; Lee, Sunyi; Lee, Eun‐Woo; Soh, Su Jung; Joo, Hyun Jeong; Sumiyasuren, Buyanravjkh; Park, Ji Young; Lim, Jong‐Seok; Park, Jong Hoon; Lee, Myung Sok; et al.
Abstract: In most mammalian cells, the primary cilium is a microtubule‐enriched protrusion of the plasma membrane and acts as a key coordinator of signaling pathways during development and tissue homeostasis. The primary cilium is generated from the basal body, and cancerous inhibitor of protein phosphatase 2A (CIP2A), the overexpression of which stabilizes c‐MYC to support the malignant growth of tumor cells, is localized in the centrosome. Here, we show that CIP2A overexpression induces primary cilia disassembly through the activation of Aurora A kinase, and CIP2A depletion increases ciliated cells and cilia length in retinal pigment epithelium (RPE1) cells. CIP2A depletion also shifts metabolism toward the glycolytic pathway by altering the expression of metabolic genes related to glycolysis. However, glycolytic activation in CIP2A‐depleted cells does not depend on cilia assembly, even though enhanced cilia assembly alone activates glycolytic metabolism. Collectively, these data suggest that CIP2A promotes primary cilia disassembly and that CIP2A depletion induces metabolic reprogramming independent of primary cilia. Synopsis: Cancerous inhibitor of protein phosphatase 2A (CIP2A) is located at the cilia transition zone and inhibits cilia assembly and the glycolytic pathway. CIP2A depletion increases ciliated cells and cilia length and enhances the glycolytic pathway. CIP2A depletion‐induced glycolytic activation is not dependent on cilia assembly. Enhanced cilia assembly activates glycolytic metabolism regardless of CIP2A. Abstract : Cancerous inhibitor of protein phosphatase 2A (CIP2A) is located at the cilia transition zone and inhibits cilia assembly and the glycolytic pathway. CIP2A depletion increases ciliated cells and cilia length and enhances the glycolytic pathway.